High arterial ligation and risk of anastomotic leakage in anterior resection for rectal cancer in patients with increased cardiovascular risk. (November 2015) - Boström, P.; Haapamäki, M. M.; Matthiessen, P.; Ljung, R.; Rutegård, J.; Rutegård, M.
Abstract Aim Controversy still exists as to whether division of the inferior mesenteric artery close to the aorta influences the risk of anastomotic leakage after anterior resection for rectal cancer. This population‐based study was carried out to evaluate the independent association between high arterial ligation and anastomotic leakage in patients with increased cardiovascular risk. Method All 2673 cases of registered anterior resection for rectal cancer from 2007 to 2010 were identified from the Swedish Colorectal Cancer Registry and cross‐referenced with the Prescribed Drugs Registry, rendering a cohort of all patients with increased cardiovascular risk. Operative charts and registered data were reviewed for 722 patients. The association between high tie and anastomotic leakage, as quantified by ORs and 95% CIs, was evaluated in a logistic regression model, with adjustment for confounding, including assessment of interaction. Results Symptomatic anastomotic leakage occurred in 12.3% (41/334) of patients in the high tie group and in 10.6% (41/388) in the low tie group. The use of high tie was not independently associated with a higher risk of anastomotic leakage (OR = 1.05; 95% CI: 0.61–1.84). In a post‐hoc analysis, patients with a history of manifest cardiovascular disease and American Society of Anesthesiologists (ASA) score III–IV seemed to be at greater risk (OR = 3.66; 95% CI: 1.04–12.85). Conclusion In the present population‐based, observational setting, high tie was not independently associated with an increased risk of symptomatic anastomotic leakage after anterior resection for rectal cancer. However, this conclusion may not hold for patients with severe cardiovascular disease.